Growth Accelerations and Reversals in Emerging Market and Developing Economies : The Role of External Conditions - Gruss, Bertrand; Nabar, Malhar; Poplawski Ribeiro, Marcos (Washington, D.C. : International Monetary Fund, 2018)
This paper investigates how country-specific external demand, external financial conditions, and terms of trade affect medium-term growth in Emerging Market and Developing Economies and the occurrence of growth accelerations and reversals. The importance of country-specific external conditions for medium-term growth has increased over time-in particular, the growing contribution of external financial conditions accounts for one-third of the increase in average income per capita growth between 1995-2004 and 2005-14. Stronger external demand and financial conditions significantly increase the probability of growth accelerations, while a strengthening of any of the three conditions significantly decreases the probability of reversals.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet